ANALISIS ECONOMIC VALUE ADDED SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA PT. PEGADIAN PERSERO CABANG TAPI BANDAR KOTA PADANG - Jesika Putri; Ruzikna ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research conducted at PT Pegadaian Persero Tapi Bandar Branch Padang City has the aim of being able to determine and evaluate financial performance from 2017 to 2021 using the Economic Value Added method. The secondary data used in this study is in the form of financial statements taken at PT. Pawnshop Persero Tapi Bandar Branch for a period of 5 years, namely 2017 to 2021. The approach in this study was also assisted by data collection through the documentation method. The analytical tools used to generate EVA value in this study are Net Operating After Tax (NOPAT), Invested Capital (IC), Weighted Average Cost Of Capital (WACC), Capital Charges (CC). The results of the study explain that the financial performance of this company is good because the EVA value is positive from 2017 to 2021, although in the last year the value of EVA has decreased from the previous year. This happened as a result of a decrease in company profits. Keywords : Economic Value Added, Financial Performance